Utility of risk scores to predict adverse events in cardiac lead extraction. (3rd October 2018) - Segreti, Luca; Giannotti Santoro, Mario; Di Cori, Andrea; Zucchelli, Giulio; Viani, Stefano; De Lucia, Raffaele; Della Tommasina, Veronica; Barletta, Valentina; Paperini, Luca; Soldati, Ezio; Bongiorni, Maria Grazia
ABSTRACT: Introduction : Increasing device implantations, patient comorbidities,  and longer life expectancy contribute to an increased need for lead extraction. Even if transvenous lead extraction (TLE) is a highly successful procedure, some serious procedural complications are reported. In order to identify those patients who are at higher risk, risk stratification scores were proposed. Areas covered : The major obstacles to lead extractions are represented by the body's response to the foreign implanted material and by the following development of fibrotic reaction between the lead and the vascular system. Several clinical factors and device features are associated with major complications and worse outcomes. Although different multiparametric scores predicting the safety and the efficacy of TLE procedures were reported, none of these scores were prospective evaluated. Expert commentary : A correct risk stratification is needed in order to refer complex patients to centers with proven experience and avoid futile procedures. Furthermore, the identification of high-risk patients allows to perform the extraction procedure in the operating room instead of electrophysiology lab. Albeit some risk scores able to predict adverse event in cardiac lead extraction were described, there are still several limitations to their use and reproducibility.